2021
DOI: 10.1186/s43094-021-00270-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of RP-HPLC method for the simultaneous determination of cetirizine in the presence of quinolones

Abstract: Background Present work describes a fast, simple, and sensitive procedure for the simultaneous determination of cetirizine in the presence of quinolones using diclofenac sodium as an internal standard. The present work was designed to analyze these compounds in pharmaceutical and clinical labs being economical for use. Results The mobile phase consisted of the simple composition of methanol, acetonitrile, and water in a ratio of 50:20:30 with a pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our procedure had a shorter retention time for both drugs than the reported HPLC procedures 12 , 13 , 16 , 27 , 30 . The developed HPLC procedure, whose mobile phase is made up of only two components, is much simpler than other documented HPLC procedures 14 , 15 , 30 , 31 , whose mobile phases are made up of three or more components, therefore requiring more time for preconditioning. Also, our procedure had a lower LOQ for both drugs than the documented procedures 13 – 16 , 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our procedure had a shorter retention time for both drugs than the reported HPLC procedures 12 , 13 , 16 , 27 , 30 . The developed HPLC procedure, whose mobile phase is made up of only two components, is much simpler than other documented HPLC procedures 14 , 15 , 30 , 31 , whose mobile phases are made up of three or more components, therefore requiring more time for preconditioning. Also, our procedure had a lower LOQ for both drugs than the documented procedures 13 – 16 , 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…BP 8 stated non-aqueous potentiometric titration with sodium hydroxide, whilst USP 10 described high performance liquid chromatography (HPLC) procedure for CTZ estimation. Various analytical techniques have been developed for the determination of CTZ either in pharmaceutical preparations, human plasma or aqueous humor as HPLC [11][12][13][14][15][16] , capillary electrophoresis 17,18 , spectrofluorimetry [19][20][21][22][23] and spectrophotometry 24,25 .…”
mentioning
confidence: 99%
“…Many methods have already been reported for estimations of ciprofloxacin [6][7][8][9][10][11][12] and but the present method is straightforward and is validated according to ICH (International Conference on Harmonization) guidelines [16]. All of the parameters were found under the limits of ICH guidelines, and the chromatogram of the analyte revealed that the method was specific and no peak of internal standard interfered, and can be considered selective.…”
Section: Resultsmentioning
confidence: 90%
“…suppositories, gels, eye drops, etc.) [6][7][8][9][10][11][12]. A direct and sensitive HPLC method for determining ciprofloxacin in the influenza vaccine has been described [7] employing a mobile phase of acetonitrile/water/phosphoric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Gradient elution Water: formic acid 0.13% (solvent A) and methanol (solvent B) 2. Expensive detector [ 8 ] HPLC–UV Pharmaceutical preparations 1–20 µg mL −1 1.0 µg mL −1 Acetonitrile: phosphate buffer pH 3.5 (40: 60 v/v) [ 9 ] HPLC–UV Pharmaceutical preparations 5–50 µg mL −1 1.9 µg mL −1 Methanol: phosphate buffer pH 3.5 (80: 20 v/v) [ 10 ] HPLC–UV Pharmaceutical preparations and human serum 2.5–50 µg mL −1 0.035 µg mL −1 Methanol: acetonitrile: water pH 3.1 (50: 20: 30 v/v/v) [ 11 ] HPLC–UV Human serum 1–100 µg mL −1 2.0 µg mL −1 Methanol: water pH 2.8 (70: 30 v/v) [ 12 ] Spectrofluorimetry Pharmaceutical preparation and human plasma 40–400 ng mL −1 8.3 ng mL −1 1. Reaction with potassium persulphate and 2-cynoacetamide in alkaline medium 2.…”
Section: Resultsmentioning
confidence: 99%